Chicken blood provides a suitable meal for the sand fly Lutzomyia longipalpis and does not inhibit Leishmania development in the gut - Sant'Anna, Mauricio RV (BioMed Central, 2010)
BACKGROUND: The aim of this study was to address the role of chickens as bloodmeal sources for female Lutzomyia longipalpis and to test whether chicken blood is harmful to Leishmania parasite development within the sand flies. Bloodmeal ingestion, excretion of urate, reproduction, fecundity, as well as Leishmania infection and development were compared in sand flies fed on blood from chickens and different mammalian sources. RESULTS: Large differences in haemoglobin and protein concentrations in whole blood (dog>human>rabbit> chicken) did not correlate with differences in bloodmeal protein concentrations (dog = chicken>human>rabbit). This indicated that Lu. longipalpis were able to concentrate bloodmeals taken from different hosts using prediuresis and this was confirmed by direct observation. Sand flies fed on chickens or dogs produced significantly more eggs than those fed on human blood. Female Lu. longipalpis retained significantly more urate inside their bodies when fed on chicken blood compared to those fed on rabbit blood. However, when the amounts of urate excreted after feeding were measured, sand flies fed on rabbit blood excreted significantly more than those fed on chicken blood. There was no difference in female longevity after feeding on avian or mammalian blood. Sand flies infected via chicken blood produced Leishmania mexicana infections with a similar developmental pattern but higher overall parasite populations than sand flies infected via rabbit blood. CONCLUSIONS: The results of this study help to define the role that chickens play in the epidemiology of leishmaniasis. The present study using a Lu. longipalpis/L. mexicana model indicates that chickens are suitable hosts to support a Lu. longipalpis population and that chicken blood is likely to support the development of transmissible Leishmania infections in Lu. longipalpis.